"I've been 95% safe": perspectives on HIV pre-exposure prophylaxis at a drug detoxification center: a qualitative study. Issue 4 (3rd April 2023) - Massey, Eugene S. G.; Bazzi, Angela R.; Sian, Carlos R.; Gebel, Christina M.; Bernstein, Judith A.; Assoumou, Sabrina A.
ABSTRACT: Pre-exposure prophylaxis (PrEP) decreases human immunodeficiency virus (HIV) acquisition among persons who inject drugs (PWID); however, its uptake has been suboptimal. We explored HIV risk perceptions and PrEP interest among drug detoxification center patients in the context of the ongoing opioid overdose epidemic. We conducted in-depth interviews of patients ( n  = 24) and professional key informants ( n  = 10 physicians, case managers, nurses, and harm reduction educators), and thematic analysis of coded data. The mean age of participants (patients) was 37 years; 54% identified as male and 67% as White. Although 71% reported injecting drugs and 62% had condomless sex in the past 6 months, participants had mixed HIV risk perceptions, and some viewed PrEP as an undesirable indicator of elevated HIV risk. Nevertheless, many participants viewed drug detoxification as a first step towards embarking on a "healthier lifestyle, " with some narratives identifying opportunities for delivering PrEP information and services in this setting. Opportunities exist to expand PrEP at drug detoxification centers, but initiatives are needed to educate patients and staff on indications and benefits of this prevention tool. Interventions are also needed to determine the best strategies for implementing PrEP adoption in this setting.